Cytotoxic, Antimitotic, DNA Binding, Photocatalytic, H2O2 Sensing, and Antioxidant Properties of Biofabricated Silver Nanoparticles Using Leaf Extract of Bryophyllum pinnatum (Lam.) Oken - Chandraker, Sandip Kumar; Lal, Mishri; Dhruve, Preeti; Singh, Rana P.; Shukla, Ravindra (Frontiers in Molecular Biosciences, 2021)
Bryophyllum pinnatum is a perennial herb traditionally used in ethnomedicine. In the present report, silver nanoparticles (AgNPs) were synthesized using B. pinnatum leaf extract. BP-AgNPs were confirmed following UV-Vis spectroscopy with SPR peak at 412 nm and further characterized by FTIR, XRD, SEM-EDX, and TEM. Microscopic images confirmed the spherical shape and ~15 nm average size of nanostructures. BP-AgNPs were evaluated for photocatalytic degradation of hazardous dyes (methylene blue and Rhodamine-B) and showed their complete reduction within 100 and 110 min., respectively. BP-AgNPs have emerged as a unique SPR-based novel sensor for the detection of H2O2, which may deliver exciting prospects in clinical and industrial areas. DPPH and ABTS free radical scavenging activity were studied with respective IC50 values of 89 and 259 μg/mL. A strong intercalating interaction of CT-DNA with BP-AgNPs was investigated. Observed chromosomal abnormalities confirm the antimitotic potential of BP-AgNPs in the meristematic root tip. The cytotoxicity of BP-AgNPs against B16F10 (melanoma cell line) and A431 (squamous cell carcinoma cell line), was assessed with respective IC50 values of 59.5 and 96.61 µg/ml after 24 h of treatment. The presented green synthetic approach provides a novel and new door for environmental, industrial, and biomedical applications.